Menghidupkan Kembali GBHN: Komparasi GBHN dan RPJPN sebagai Kebijakan Politik Hukum Nasional dalam Bidang Pembangunan - Bahaudin, Bahaudin (Jurnal Keamanan Nasional, 2017)
Political law of development policies in the Reformation era no longer recognized the term National Directives Outline (Garis-Garis Besar Haluan Negara or GBHN). Reformation planners consider the terminology as taboo because of its close association with the New Order (Orde Baru) regime. The Reformation era acknowledges the term Long Term Development Plan (Rencana Pembangunan Jangka Panjang or RPJP) as the political law of national development policies. In practice, RPJPN is the vision and mission of the elected President and has a limitation of 10 years, exceeding the President’s term of office. Unlike GBHN which is constitutional and bound to be executed regardless of who is leading, RPJP is political and compromising in nature and, therefore fraught with inconsistencies. This article discusses GBHN and the proposed revival of it as the national development directive.